Rottlerin promotes anti-metastatic events by ameliorating pharmacological parameters of paclitaxel: An in-vivo investigation in the orthotopic mouse model of breast cancer - Manhas D.; Mir K.B.; Tripathi N.; Bharti S.; Dhiman S.; Wazir P.; Sharma D.K.; Goswami A.; Nandi U. (My University, 2025)
Despite substantial breakthroughs in cancer research, there is hardly any specific therapy available to date that can alleviate triple-negative breast cancer (TNBC). Paclitaxel is the first-line chemotherapy option, but its treatment is often associated with early discontinuation of therapy due to the development of resistance and/or precipitation of severe side effects. In the quest to establish a suitable combination therapy with a low dose of paclitaxel, we explored rottlerin (a pure and characterized phytoconstituent from Mallotus philippensis) because of its multifaceted pharmacological actions against cancer. The study was performed to assess the therapeutic effects of rottlerin (5–20 mg/kg) with a low dose of paclitaxel (5 mg/kg) using a highly aggressive mouse mammary carcinoma model. Rottlerin augmented the paclitaxel effect by reducing tumor burden as well as metastatic lung nodules formation. Rottlerin in combination with paclitaxel remarkably altered the expression of vital epithelial-mesenchymal transition (EMT) markers such as E-cadherin, Snail 1, & Vimentin and thus improved the anti-metastatic efficacy of paclitaxel. Significant attenuation of anti-apoptotic protein (Bcl-2) along with amplification of pro-apoptotic (cleaved PARP) marker confers that rottlerin could ameliorate the pro-apoptotic potential of paclitaxel. In this study, a rational combination of rottlerin and paclitaxel treatment curtailed CYP2J2 expression and epoxyeicosatrienoic acids (EETs) levels, responsible for restrain tumor growth and metastasis. Additionally, rottlerin lessened paclitaxel treatment-mediated hematological alterations and prevented paclitaxel treatment-linked key serum biochemical changes related to organ toxicities. These rottlerin treatment-mediated protective changes are closely associated with the lower paclitaxel accumulation in the corresponding tissues. Rottlerin caused significant pharmacokinetic interaction with paclitaxel to boost the plasma level of paclitaxel in a typical mouse model and possibly helpful towards the use of a low dose of paclitaxel in combination. Overall, it can be stated that rottlerin has significant potential to augment the anti-metastatic efficacy of paclitaxel via impeding EMT activation along with attenuating its treatment-associated toxicological alterations. Hence, rottlerin has significant potential to explore further as a suitable neoadjuvant therapy with paclitaxel against TNBC. © 2022 Elsevier B.V.